Description of Motor Skill Development and Parent Socio-Economic Status of West Java Little League Baseball Athletes - Sumarno, Gano; Situmorang, Andi Suntoda; Stephani, Mesa Rahmi; Wibowo, Ricky (TEGAR: Journal of Teaching Physical Education in Elementary School, 2021)
Elite sport achievement in early childhood is inseparable from parent financial supports. In Little League Baseball sport, parents invest money to help their children grow and develop optimally. Parents put their hopes and aspirations for their children to become a great Indonesian Baseball player. This study aimed at determining the socioeconomic status characteristics of the Little League Baseball athlete parents in West Java. This study used a cross-sectional study method. Sixteen parents volunteered to fill out the Social Economic Status questionnaire via Google Form. Data were analysed using percentage techniques and Spearman correlation test. The results showed that the Socio-Economic Status (SES) of the Little League Baseball athlete parents was in the middle to upper category. The athlete motor development was at a good level. The socio-economic status condition of the Little League Baseball athlete parents, who were included in the middle to upper category, had a beneficial effect on the optimal training process because the training demand fulfilment requires a financial support.